Acrodermatitis continua of Hallopeau successfully treated with secukinumab. (30th November 2018) - Balestri, Riccardo; Rech, Giulia; Tasin, Laura; Rizzoli, Laura; Girardelli, Carlo Renè
Abstract: Acrodermatitis continua of Hallopeau is considered an uncommon variant of pustular psoriasis, characterized by a relapsing, sterile, pustular eruption of hands and feet. It is not easily treated by antipsoriatic therapies, and may progress toward sclerosis and osteolysis. Numerous topical and systemic treatments have been used, with inconsistent results. The therapeutic response of pustular psoriasis to biologics supports the pivotal role of the tumor necrosis factor (TNF)-α/interleukin (IL)-23/IL-17/IL-22 axis in the pathogenesis of the disorder. Based on these data, secukinumab was used in a patient with uncontrolled acrodermatitis continua of Hallopeau. We described a case of secukinumab treated patient with uncontrolled acrodermatitis continua of Hallopeau. Our experience suggests that secukinumab may represent a suitable choice for the management of acrodermatitis continua of Hallopeau resistant to other treatments.